2013
DOI: 10.1016/j.nut.2012.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cross-over randomized trial method to determine the acceptability and safety of novel ready-to-use therapeutic foods

Abstract: Development of a cross-over randomized trial method to determine the acceptability and safety of novel ready-to-use therapeutic foods Objective: To develop a method for determining the acceptability and safety of ready-to-use therapeutic foods (RUTF) before clinical trialing. Acceptability was defined using a combination of three consumption, nine safety, and six preference criteria. These were used to compare a soy/ maize/sorghum RUTF (SMS-RUTFh), designed for the rehabilitation of human immunodeficiency viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
2
16
0
1
Order By: Relevance
“…Similar to the findings from Kenya,15,26 we found that patients reported complaints about the unfamiliar taste of RUSF. In Kenya, it was common to mix RUSF with local foods to overcome unwanted taste and dietary monotony.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the findings from Kenya,15,26 we found that patients reported complaints about the unfamiliar taste of RUSF. In Kenya, it was common to mix RUSF with local foods to overcome unwanted taste and dietary monotony.…”
Section: Discussionsupporting
confidence: 88%
“…In Malawi, 92.4% of participants reported consuming the recommended amount (140 g) the day prior to clinical visit [26], while in Ethiopia, 74% reported eating the recommended portion (200g LNS+30g whey or soy protein) in the prior three days [46]. In Kenya, participants in a cross-over randomized control trial ate more than 75% of the daily dosage of peanut-based LNS (250g) on 87.7% of days under direct observation (compared to 86.1% of days for a soy maize blend) [42]. In Ghana, 96% of participants reported consuming the recommended 20g “every time” [17].…”
Section: Discussionmentioning
confidence: 99%
“…They include soybeanmaize-sorghum ready-to-use therapeutic food (SMS RUTF), soybeanmaize-sorghum ready-to-use supplementary foods (SMS RUSF) and soybean-maize-sorghum ready-to-use complementary food (SMS RUCF). Acceptability and efficacy of SMS-RUF have been tested for treatment and prevention of malnutrition [13][14][15] among children in resource poor settings. The impact of consumption of SMS-RUCF on breast milk intake has also been assessed [16].…”
Section: Introductionmentioning
confidence: 99%